2014
DOI: 10.1128/cvi.00812-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Use of a Serum Bactericidal Assay Using Pooled Human Complement To Assess Responses to a Meningococcal Group A Conjugate Vaccine in African Toddlers

Abstract: A meningococcal group A polysaccharide (PS) conjugate vaccine (PsA-TT) has been developed for African countries affected by epidemic meningitis caused by Neisseria meningitidis. Complement-mediated serum bactericidal antibody (SBA) assays are used to assess protective immune responses to meningococcal vaccination. Human complement (hC=) was used in early studies demonstrating antibody-mediated protection against disease, but it is difficult to obtain and standardize. We developed and evaluated a method for sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Here whole pathogens, components, or epitope-scaffolds can be individually coupled to beads, with simply coupling adaptions, to fully interrogate the response. Furthermore, the requirement for fresh human plasma as the gold standard in SBA reduces throughput and may introduce variation (Bash et al, 2014), even though we have shown that human complement is comparable across donors. Conversely, the high-throughput assay described here can be adapted for profiling of almost any antigen, including glycan-, lipid-, or protein-based antigens, that may be coupled to a bead in a sample-sparing, robust, and reproducible manner.…”
Section: Discussionmentioning
confidence: 99%
“…Here whole pathogens, components, or epitope-scaffolds can be individually coupled to beads, with simply coupling adaptions, to fully interrogate the response. Furthermore, the requirement for fresh human plasma as the gold standard in SBA reduces throughput and may introduce variation (Bash et al, 2014), even though we have shown that human complement is comparable across donors. Conversely, the high-throughput assay described here can be adapted for profiling of almost any antigen, including glycan-, lipid-, or protein-based antigens, that may be coupled to a bead in a sample-sparing, robust, and reproducible manner.…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous complement SBA assay was performed in 96‐well plates as previously described (Bash et al ., ) with slight modifications. Briefly, hybrid or OMP deletion strains were incubated at 37°C with shaking (65 rpm) in the presence of twofold dilutions of Z15 mAb (in 0.5% BSA in Hank's Buffered Saline Solution) and pooled human sera that had been pre‐screened for lack of endogenous killing activity.…”
Section: Methodsmentioning
confidence: 99%
“…SBA is used to quantify the levels of antibodies that are specific for bacterial surface determinants and results in complement-mediated lysis of bacteria (25). SBA in vitro is considered as the gold standard test for the evaluation of functional anti-meningococcal antibodies and as an accepted surrogate for protection (26).…”
Section: Discussionmentioning
confidence: 99%